Omega-3 fatty acids mediate immune regulation anticancer mechanisms by il-6, 5 (s)- hete and ros generation in pancreatic human cells - Garay, María Isabel (2017)
Fil: Garay, María Isabel. Universidad Nacional de Córdoba. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones en Ciencias de la Salud; Argentina.